Ethical-legal implications of AI-powered healthcare in critical perspective - Nasir, Mohammad; Siddiqui, Kaif; Ahmed, Samreen (Frontiers in Artificial Intelligence, 2025)
The increasing utilization of Artificial Intelligence (AI) systems in the field of healthcare, from diagnosis to medical decision making and patient care, necessitates identification of its potential benefits, risks and challenges. This requires an appraisal of AI use from a legal and ethical perspective. A review of the existing literature on AI in healthcare available on PubMed, Oxford Academic and Scopus revealed several common concerns regarding the relationship between AI, ethics, and healthcare—(i) the question of data: the choices inherent in collection, analysis, interpretation, and deployment of data inputted to and outputted by AI systems; (ii) the challenges to traditional patient-doctor relationships and long-held assumptions about privacy, identity and autonomy, as well as to the functioning of healthcare institutions. The potential benefits of AI’s application need to be balanced against the legal-ethical issues emanating from its use—bias, consent, access, privacy and cost—to guard against detrimental effects of uncritical AI use. The authors suggest that a legal framework for AI should adopt a critical and grounded perspective—cognizant of the material political realities of AI and its wider impact on more marginalized communities. The largescale utilization of health datasets often without consent, responsibility or accountability, further necessitates regulation in the field of technology design, given the entwined nature of AI research with advancements in wearables and sensor technology. Taking into account the ‘superhuman’ and ‘subhuman’ traits of AI, regulation should aim to encourage the development of AI systems that augment rather than outrightly replace human effort.